Injury as a Result of Children and Adolescent Labor-An Association with Ethnicity and Peripherality: A Retrospective Cohort Study Based on the Israeli Trauma Registry - Bella Savitsky; Irina Radomislensky; Eldad Katorza; Arielle Kaim (MDPI AG, 2023)
Background: Working children and adolescents face a heightened risk of work-related injuries. This research aimed to assess the rate of hospitalizations resulting from work-related injuries among children and adolescents in Israel, with a specific focus on disadvantaged populations. Methods: This nationwide retrospective cohort study utilized The Israeli National Trauma Registry (INTR). It included 642 children and adolescents aged 13-17 hospitalized due to work-related injuries from 2015-2022. Results: Arab children had over five times the risk of hospitalization due to work-related injuries compared to Jewish (RR = 5.5, 95% CI: 4.7-7.4). Despite the 2018 law prohibiting young people from entering this type of work, the most common type of work leading to hospitalization was construction, accounting for 40.2% of Arab and 11.9% of Jewish injuries (p < 0.001). After adjustment, road traffic accidents and falls presented the highest odds of at least severe injury. Arabs had three times significantly higher odds of at least moderate injury compared to Jews. Conclusions: Prioritizing the creation of safe job opportunities for Arab teenagers is imperative. Strict enforcement measures, particularly within the construction industry, especially among Arab youth and during night shifts, are essential. These initiatives should focus on establishing secure and sustainable employment opportunities for children and young individuals, effectively reducing the risks associated with hazardous labor practices. In addition, the implementation of educational programs in the school curriculum covering essential aspects of youth employment is vital.